DIGITAL LITERACY AS A MODERATOR OF THE INFLUENCE OF INFLUENCER AND DIGITAL MARKETING ON CONSUMER PURCHASE DECISIONS IN THE HIJABQA FASHION BUSINESS - Wijayanti, Renata (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2025)
The purpose of this study is to investigate how customer purchasing decisions are impacted by digital and influencer marketing, as well as how digital literacy functions as a moderating factor in the HijabQA fashion industry. The research used a quantitative approach with purposive sampling involving 50 Shopee customers who met specific purchase criteria. The Structural Equation Modeling–Partial Least Square (SEM–PLS) method was used to evaluate the Likert-scale questionnaire that was disseminated online. The findings indicate that purchasing decisions are significantly impacted by influencer marketing, while digital marketing has no significant effect. Furthermore, the association between the two marketing methods and purchase decisions is not moderated by digital literacy. These findings indicate that consumer trust in influencers plays a stronger role in influencing buying behavior than traditional digital promotions. The implication is that fashion businesses like HijabQA should focus more on building strategic collaborations with relevant influencers as a more effective marketing approach.